An Assessment of Soil Fertility and Capability Potentials of Derived Savanna Landscapes in Delta State: Implication of Suitability for Arable Farming - Edewor Akpezi Okiemute (Journal of Agribusiness and Natural Resources, 2025)
This research paper examined the soil fertility and capability potentials of derived savanna landscapes in Delta State: implication on suitability for food security. The derived savannas of Delta State are vegetation with peculiar land cover because they are adjudged as alien vegetation that exists within the rainforest which is outside the domain of “savanna” grasslands which occurs in the middle belt as Guinea savanna Sudan and Sahel savanna in northern Nigeria. They are termed derived savannas because they are environmental derivatives of anthropogenic disturbances and other factors of nature within the rainforest. Over the years, the derived savannas have either been marginalized, idle or underutilized, as they are either touched by wild bush fires, during the dry seasons or flooded during the wet seasons. The assessment of the soil fertility and capability status of the derived savanna therefore confirmed that they are rich in major soil parameters such as organic carbon content, nitrogen, potassium and others. They are also suitable for hydrotolerant plants. The study justified the derived savanna of Delta State as having the fertility and capability potential to support sustainable ventures for arable farming and general agricultural land use. This is especially true for short-term crops that can mature before the annual flood regime. Also, their usage for arable farming practices will ameliorate food insecurity in the area based on the recommendation of the soil suitability for arable farming.